Tradisi Ngusaba Lampuan Di Desa Pakraman Bayunggede Kecamatan Kintamani Kabupaten Bangli (Perspektif Pendidikan Agama Hindu) - Ni Luh Eka Yanti (Jurnal Penelitian Agama Hindu, 2019)
The uniquenss of Lampuan Ceremony is held every four years which invoies the Daha (The Girl) and Truna (The Youngs) of Bayunggede Village. They must wear clotehes that are already prepaed by the elders of the Village. Based on the data analysis that was carried out, the reseacher knows that the first ceremony in the procession of Ngusaba Lampuan is Matur piuning/ Ngampuh (to offer on offering to God) in Penataran Bintak Temple, the second religious and ceremony is melasti/ Metirtaan (a Hindu Baliness purification ceremony and ritual) that is held in Pondokan Susut Temple, and the offerings that are offered is penyeneng/ peras pejati. The thrid ceremony is Matur Piuning in Puseh Pingit Temple by offering Banten Tamus, The fourth ceremony is Puncak Karya, the village pray together and the last ceremony called Penyindeban/ Pamuput Karya. This ceremony ends the procession of Ngusaba Lampuan ceremony of Desa Pakraman in Bayunggede Village tahat located in Kintamani Disctrict od Bangli Regency. There are four fungcion of Ngusaba Lampuan : (1) Religious (2) Social function (3) Ethical function (4) Ritual function. There are also three values of Ngusaba Lampuan tradition, they are (1) Tatwa value (2) Value of Moral (ethical) and (3) The value of Moral education (ethical) and (3) the value Education in religius ceremony (ritual).